2020
DOI: 10.1038/s41598-020-73531-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of remote imaging photoplethysmography and cutaneous perfusion in volunteers

Abstract: Remote imaging photoplethysmography (iPPG) senses the cardiac pulse in outer skin layers and is responsive to mean arterial pressure and pulse pressure in critically ill patients. Whether iPPG is sufficiently sensitive to monitor cutaneous perfusion is not known. This study aimed at determining the response of iPPG to changes in cutaneous perfusion measured by  Laser speckle imaging (LSI). Thirty-seven volunteers were engaged in a cognitive test known to evoke autonomic nervous activity and a Heat test. Simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
(44 reference statements)
0
9
0
1
Order By: Relevance
“…PPG has previously shown potential to be used in a camera-based intraoperative setting 26 , where data from the green channel could estimate the heart rate in 95.6% of cases. rPPG has been shown to be closely associated with cutaneous perfusion and sensitive to autonomic nervous activity 27 . A correlation of 0.91 has been shown between PPG and one of the main technologies for studying microcirculation, laser Doppler flowmetry, for endothelial activities 28 .…”
Section: Introductionmentioning
confidence: 99%
“…PPG has previously shown potential to be used in a camera-based intraoperative setting 26 , where data from the green channel could estimate the heart rate in 95.6% of cases. rPPG has been shown to be closely associated with cutaneous perfusion and sensitive to autonomic nervous activity 27 . A correlation of 0.91 has been shown between PPG and one of the main technologies for studying microcirculation, laser Doppler flowmetry, for endothelial activities 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Since the propagation of green light into the skin is circumscribed to about 1 mm [37,38], the hemodynamic information content of iPPG is specific for the cutaneous microcirculation. Though not a direct measure, iPPG signals are strongly associated to cutaneous perfusion [13].…”
Section: Discussionmentioning
confidence: 99%
“…The iPPG signal is affected by autonomic nervous activity and vasomotor control in the peripheral vascular bed, such as in reactions to hot and cold thermal stimuli [8,9], topically induced cutaneous vasodilation [10,11], the vasodilatory effects of regional anaesthesia and reactive hyperaemia after vascular occlusion [11]. The blood volume pulse detected by iPPG is seen as an indirect measurement of skin perfusion [1,12,13]. This idea has been implemented in studies assessing burn wounds [14] and free flaps in plastic surgery, [15] or to reveal changes in the microcirculation of the skin associated with migraine [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…iPPG offers a solution to use a regular camera [ 26 ], a surveillance camera, or even a mobile camera to capture PPG from the face, forehead, chest, finger, or any exposed skin from different body parts. iPPG discovery opened up a new field of research and played an important role in remote patient monitoring experiments [ 14 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. Deep learning hype is also brought to the field of iPPG [ 14 , 15 ].…”
Section: Diagnostic Features and Their Clinical Usagesmentioning
confidence: 99%
“…iPPG was used to detect blood flow changes during thermal exposure to the skin [ 28 ]. It is also found that iPPG is also associated with cutaneous perfusion [ 32 ].…”
Section: Diagnostic Features and Their Clinical Usagesmentioning
confidence: 99%